Feasibility of nickel extraction from Indian chromite overburden by solid state reduction and smelting route - Ganesh P.; Kumar Dishwar R.; Agrawal S.; Kumar Mandal A.; Sahu N.; Sinha O.P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present work demonstrates the extraction of nickel from low-grade chromite overburden by using solid state reduction and direct smelting route. Goethite & Quartz are present as major phases whereas chromite, hematite were identified as minor phases in the mineral. Solid state reduction of pellets were carried out inside a horizontal tube furnace at 1000°C, 1200°C, 1400°C for 30, 60, 90 and 120 minutes respectively with creating reducing atmosphere. Pellets of varying basicity (i.e. 0.5, 0.6, 0.7, 0.8 and 0.9) were used directly in the EAF for smelting studies. Highest percent of nickel (2%) having ~ 91% recovery were obtained in solid state reduction route for pellets which was reduced at 1400°C for 120 minute. Similar recovery (~90%) of nickel was obtained inside the ingot (0.67% Ni ) by using pellets of 0.9 basicity through smelting route. From the present investigation, it could be concluded that the solid state reduction as well as smelting routes are feasible for the recovery of nickel from low grade chromite overburden. The production of nickel pig (low grade ferronickel) could also be feasible by smelting route.